Study of near scrape-off layer (SOL) temperature and density gradient lengths with Thomson scattering. (3rd November 2015) - Sun, H J; Wolfrum, E; Eich, T; Kurzan, B; Potzel, S; Stroth, U
Abstract: Improvements to the Thomson scattering diagnostic have enabled the study of near scrape-off layer (SOL) decay lengths in the 2014 ASDEX Upgrade experimental campaign. A database of H-mode discharges has been studied using a two-line fit method for the core and log-linear fit for the near SOL region under both attached and detached divertor conditions. SOL electron temperature profiles have been found to have a radial exponential decay distribution which does not vary poloidally, consistent with the two-point model. In attached H-mode regimes, a log-linear regression shows that the SOL upstream dataset has the same main parametric dependencies as the scaling inferred from downstream Infrared camera measurements. A simple collisional relation from two-point model is found to best relate the upstream decay lengths and downstream divertor power widths. The SOL gradient length appears to be independent of pedestal parameters, but may correlate with the pedestal electron pressure parameters. Both the pedestal and SOL density and temperature scale lengths are linearly correlated with an almost constant gradient ratio, . The smaller gradient ratio and the fact that the Spitzer–Härm model is more valid, agrees with the studied plasma lying in the collisional regime. A transition to flat SOL ne profiles, previously reported for L-mode plasmas in many machines, has been observed in AUG detatched H-mode regimes. When the flattening of density profile happens in H-mode detached plasmas, the broadening of near SOL decay length also appears which may be good news for future machines.